Infectious Diseases and Your Health (Springer Singapore, 2018)
Infectious Diseases and Your Health has the potential to impact and improve your life, and the lives of your loved ones. Every day, nearly 40, 000 people including small children and women die of infectious diseases. Many of these innocent lives could be saved. Your journey through the pages of this book will take you to an amazing world of infectious diseases. You will learn about various infectious diseases, how they can affect your life, the problems associated with their treatment and prevention, and how to overcome these problems. Additionally, you will hear the success story of new drug research, be introduced to the hard facts, and find fascinating pictures of microorganisms and parasites. The book provides instant solutions to several of your concerns about infectious diseases, and you will learn to live a highly productive, long and healthy life. So, join thousands of readers of this book worldwide, enhance your life and the lives of your loving family, become an informed healthy citizen, and contribute to achieving the UN's Sustainable Development Goals. Let us never forget: life and quality of life are very precious.